PROFITABILITY DETERMINANTS OF COMMERCIAL BANKS: A CASE STUDY OF INDONESIAN COMMERCIAL BANKS - Rumangu, Mac J.; Lambey, Linda .; Tumiwa, Johan R. (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Indonesian banking industry plays a critical role in the country economic condition. The country depends on banks as financial intermediation. Starting from 2010, commercial banks total asset and credit distribution grew significantly. The banks are expanding in order to reach more customer. The expansion makes commercial banks to operate with high cost to keep up with the development. Another problem arises as the economic contraction in 2012 affects credit growth and banks’ non-performing loan began to rise in 2014. Commercial banks’ profitability with ROA as the proxy, has been in positive trends since 2008 declined in 2013 and continues for the next years. This research aims to examine the profitability determinants of Indonesian commercial banks during the 2010-2015 period. Sample of 71 commercial banks and panel data regression with fixed effect is used in the analysis. This study finds commercial banks’ profitability as seen by ROA has been declining for some years since 2013. The high operating cost due to the expansion state and the increase of nonperforming loan cause inefficiency and decline in ROA. Net interest margin affects ROA positively while capital to total asset ratio shows a negative relationship. Total asset and diversification income insignificantly affect profitability.Keywords: profitability, commercial banks, roa (Return on Asset), efficiency